Justice in urban nature-based solutions: A systematic review of distributive, recognition, and procedural dimensions - Collier, Marcus (Elsevier, 2026)
Nature-based Solutions (NbS) have become central to urban climate adaptation agendas, yet their capacity to advance environmental justice remains underexplored. While justice has emerged as a key concern in NbS debates, no systematic synthesis has examined how its three dimensions, distributive, recognition, and procedural, are empirically addressed in urban research. This review analyzes 72 peer-reviewed studies published between 2016 and 2025, mapping how justice is framed, referenced, and translated across diverse methodologies and contexts. Findings reveal that NbS scholarship remains dominated by biophysical indicators and ecological performance metrics, while justice is often invoked but unevenly integrated into analytical frameworks. Distributive justice appears mainly through spatial proxies of access and benefit allocation; recognition justice surfaces in critiques of technocratic framings and epistemic exclusion; and procedural justice is typically confined to participation narratives without co-decision. Our synthesis identifies three structural tensions - technocratic, epistemic, and participatory - that constrain the transformative capacity of NbS, revealing how ecological bias and power asymmetries persist in research and practice. For policy and planning realm, embedding justice as a guiding criterion for diagnosis, design, and monitoring is essential to align NbS with socially sustainable urban transitions. By bridging debates, this review reframes justice as a precondition for legitimacy and effectiveness in nature-based urban transformations.
PUBLISHED
Keywords: Environmental justice; Distributive justice; Recognition justice; Procedural justice; Urban nature-based solutions; Public participation; Global south; Inclusive Society; International Development; Smart & Sustainable Planet; Biodiversity; Biodiversity and Conservation; CLIMATE CHANGE; Distributive Justice; Environmental Restoration/Remediation; Environmental planning and sustainable development; NATURE-BASED SOLUTIONS; Procedural Justice; Recognition Justice; SYSTEMATIC REVIEW; Transitional Justice; Urban Geography; Advocacy and political participation; Culture; Environment and housing; Gender; Justice and safeguarding; Policy; Social exclusion; Social participation